On some exponential decay estimates for porous elastic cylinders - Chiriță, S. (Archives of Mechanics, 2004)
In this paper we introduce two new cross-sectional measures for studying the spatial behaviour of the solutions in elastostatics of the porous cylinders. This allows us to extend the range of applicability of the estimates describing the Saint-Venant's decay behaviour of enlarged classes of porous materials.